Aplikasi Kasir Pada Adibah Boutique Berbasis Desktop - Zaid Romegar Mair; Helen Yunita Sari (Jurnal Nasional Ilmu Komputer, 2021)
Computers as human aids have advantages including speed, accuracy, and efficiency in data processing compared to manual systems. Computers have spread in various fields, both in the world of education and the world of work, including in the field of sales. Adibah Boutique has problems in terms of, among others, the irregularity of the management system, especially profit and loss, sales calculations (transaction activities), data collection of goods and preparation of sales reports still using manuals, cashier operators still use worksheet applications to complete each work activity, thus providing the impression of an impact that is less effective and efficient in terms of time and energy generated every day. Another problem in terms of the goods coding system and the absence of evidence between the seller and the buyer after the transaction raises a very basic problem, one solution is to use a desktop-based application that can manage sales information systems more easily thereby reducing the problems that occur in The Adibah Boutique. This application can be used as a commercial medium by the owner or staff of Adibah Boutique to make it easier to make sales transactions to consumers.